2021
DOI: 10.3390/plants10010139
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Seedling Grow-Out Experiments Do Not Support Seed Transmission of Sweet Potato Leaf Curl Virus in Sweet Potato

Abstract: Sweet potato leaf curl virus (SPLCV) threatens global sweet potato production. SPLCV is transmitted by Bemisia tabaci or via infected vegetative planting materials; however, SPLCV was suggested to be seed transmissible, which is a characteristic that is disputed for geminiviruses. The objective of this study was to revisit the validity of seed transmission of SPLCV in sweet potato. Using large-scale grow-out of sweet potato seedlings from SPLCV-contaminated seeds over 4 consecutive years, approximately 23,034 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Contrary to our expectation, market seeds were more infected than seeds collected from the field, indicating variation in the amount of virus inoculum in seeds. Conflicting results obtained for the same cultivar from two different sources in our study are similar to previous results [ 11 , 26 , 27 , 28 , 29 ]. This discrepancy in the virus detection between different sources, different batches of the same cultivar, and different cultivars of the same host may explain the ambiguity recorded in seed transmission of some of the begomoviruses.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to our expectation, market seeds were more infected than seeds collected from the field, indicating variation in the amount of virus inoculum in seeds. Conflicting results obtained for the same cultivar from two different sources in our study are similar to previous results [ 11 , 26 , 27 , 28 , 29 ]. This discrepancy in the virus detection between different sources, different batches of the same cultivar, and different cultivars of the same host may explain the ambiguity recorded in seed transmission of some of the begomoviruses.…”
Section: Discussionsupporting
confidence: 89%
“…The seed to seedling transmission rate was reported to be 21.21% and further confirmed the SPLCV replication in seedlings through Southern blot hybridization. On the contrary, in another study, Andreason et al (2021) concluded that SPLCV was not seed transmissible. They observed the presence of SPLCV only on the seed coat but not on any new germinated cotyledons after testing the infected seeds in Petri dishes.…”
Section: Past Knowledge Of Begomovirus Seed Transmissionmentioning
confidence: 90%
“…By contrast, other studies generally carried out more recently were not able to detect seed transmission of a number of begomoviruses, some of them previously reported as being transmissible. These include sweet potato leaf curl virus in sweet potatoes, TYLCV in tomatoes and Nicotiana benthamiana, TYLCSV in tomatoes, ToLCNDV in melons, tomato mottle virus in tomatoes, tomato golden mosaic virus in tomatoes, and bhendi yellow vein mosaic virus in okra [80][81][82][83][84][85][86].…”
Section: To Seed or Not To Seed: The Open Question Of Begomovirus See...mentioning
confidence: 99%